Surgical Management of Severe Abdominal Trauma Patients in the Surgical Department of the Toamasina CHU, Madagascar - Razafindraibe Vanona Barijaona; Rasataharifetra Hanta; Jonatana Arthur Daniel; Samison Luc Herve; Rakotoarijaona Armand Heriniriana (Newinera Publisher, 2023)
Severe abdominal trauma represents an absolute surgical emergency. The objective of our study is to report the surgical management of severe abdominal trauma in a low-resource center. This was a 31-month observational study from January 2018 to August 2020. We have 44 cases of severe abdominal trauma. The sex ratio was 4.5. The mean age of patients with severe abdominal trauma was 31.43182 years. A penetrating wound to the abdomen was seen in 68.18%. The circumstance of the trauma was a liability accident in 70.45%. A shortened laparotomy was performed. The mean duration of the operation was 45.63636 minutes. No perioperative death was reported during the performance of the shortened laparotomy. Controlling emergency surgery improves the vital prognosis of polytrauma patients.